Strategi Pengembangan Ekonomi Kreatif Subsektor Kriya Di Desa Banyuning, Kecamatan Buleleng Bali - Gunawan, Putu Agus; Prajanti, Sucihatiningsih Dian Wisika; Setyadharma, Andryan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to analyze the development strategies of the creative economy in the craft subsector in Banyuning Village, Buleleng District, Bali, focusing on three main aspects: production, marketing, and human resource development (HRD). Using a qualitative method with a descriptive design and a case study approach, this research explores current phenomena through interviews, observations, documentation, and questionnaires. Data validity was checked using source triangulation, and data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, data display, and verification. The research findings indicate that the development strategy for production requires efficiency and innovation in production techniques, improvement in product quality, and the adoption of environmentally friendly practices. However, there are challenges in capital and technology assistance that are not aligned with the needs of local practitioners. In marketing, the main challenges are the lack of market information access and negotiation capacity, which can be addressed through product diversification, extensive promotion, and the socialization of branding and independent export guidance. For HRD, priorities are given to training and skill development, building an organizational culture that supports collaboration and innovation, and policies that support employee welfare and motivation. This research uses the Analytic Hierarchy Process (AHP) to determine the priority strategies for development. The results show that the three main priorities for production are maintaining sustainability with environmentally friendly practices, product diversification, and adopting the latest technology. In marketing, the priorities are opening profitable market opportunities, extensive promotion, and the socialization of branding and independent export guidance. For HRD, the priorities are employee training and development, building a culture of collaboration and innovation, and policies supporting employee welfare and motivation. With the right strategies and well-planned implementation, it is hoped that the craft industry in Banyuning Village can develop sustainably, contribute positively to the local economy, and preserve environmental sustainability and cultural heritage.